FREEDOM Trial Analysis: Denosumab Discontinuation and Associated Fracture Incidence - Rizzo, Toni (MD Conference Express, 2012)
Patients with osteoporosis who discontinue denosumab have transient increases in bone remodeling and decreases in bone mineral density [Miller PD et al. Bone 2008; Bone HG et al. J Clin Endocrinol Metab 2011], but the effect of discontinuation on fracture risk is not clear. The Phase 3 Fracture Reduction Evaluation of Denosumab in Osteoporosis Every 6 Months [FREEDOM; NCT00089791] trial determined the incidence of fractures in postmenopausal patients with osteoporosis after stopping denosumab therapy.